Non-Formal Education as Community Empowerment in the Digital Era: A Case Study of the Digital Literacy Program for the Kalirejo Village Community, Gresik Regency - Linda Fajarwati; Muhammad Irfan Hilmi; Deditiani Tri Indrianti; Sylva Alkornia (FKIP, Universitas Palangka Raya, 2026)
The development of digital technology has brought major changes to people's lives, including in the fields of education, economics, and social life. However, many people are still unable to utilize digital technology optimally, especially communities in remote areas. This study aims to analyze the role of out-of-school education as a solution for community empowerment in the digital era. This study uses a qualitative approach. While this type of research uses case studies. Case studies are empirical methods that investigate contemporary phenomena in real-life contexts, especially when the boundaries between phenomena and contexts are unclear. The results of the study indicate that out-of-school education has a strategic role in improving people's digital skills through technology-based training, courses, and empowerment programs. Out-of-school education is also able to improve the quality of human resources, expand digital economic opportunities, and reduce the digital divide in society. Thus, out-of-school education is a relevant and flexible educational alternative in facing the challenges of the digital era.